LOCAL INSTITUTIONAL CAPACITY IN MANAGING POTENTIAL NATURAL RESOURCE CONFLICTS IN INDIGENOUS TERRITORIES OF BANDUNG REGENCY - Yans Kurnia Mahardika; Dede Sri Kartini; Antik Bintari (SOSIOEDUKASI, 2026)
Natural resource conflicts in Indigenous territories represent complex governance challenges shaped by overlapping land claims, development pressures, and socio-cultural dynamics. In Indonesia, the limited formal recognition of customary territories and the persistence of agrarian conflicts indicate structural weaknesses in preventive conflict governance. This study examines the institutional capacity of the Regional Early Warning Team (Tim Kewaspadaan Dini Daerah/TKDD) in Bandung Regency in managing potential natural resource conflicts within Indigenous territories through a collaborative governance framework. Using a qualitative research design, data were collected through in-depth interviews, field observations, and document analysis, and were analyzed using an interactive model of data reduction, display, and conclusion drawing. The findings reveal that TKDD functions as a cross-sectoral collaborative arena facilitating early detection, collective analysis of potential threats, and the formulation of preventive policy recommendations. Bakesbangpol plays a critical facilitative leadership role in coordinating actors and sustaining inter-sectoral communication. However, the effectiveness of TKDD is constrained by limited human resource capacity, fragmented data systems, relational dynamics among stakeholders, and budgetary limitations. The study demonstrates that collaborative governance in early warning mechanisms depends not only on formal institutional design but also on leadership quality, institutional capacity, and inclusive stakeholder engagement. This research contributes to the empirical understanding of collaborative governance in managing latent natural resource conflicts at the local level and highlights the importance of strengthening institutional capacity to achieve inclusive and sustainable conflict governance in Indigenous contexts.